E-Module with Flip Pdf Professional-based QR Code on Islamic Religious Education Learning - Suci Prihatiningtyas; Ainul Muslimatul Jannah; Dian Kusuma Wardani; Asiyah Lu’lu’ul Husna (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Educators must be able to design learning by combining the use of information technology into learning. One of the uses of technology in the 2013 curriculum is the use of learning resources in the form of teaching materials. One of the teaching materials in accordance with the development of digital era technology is electronic modules. This study aims to determine the feasibility of learning media and find out the response of students after using E-Module with Flip PDF Professional based on QR Code on PAI Materials at SMAN Plandaan Jombang. This research is a research and development (R&D) with Borg & Gall models. This study uses seven steps, namely Potential and Problems, Collecting Data, Product Design, Design Validation, Design Revision, Product Testing, and Product Revision. The data collected in this study were data from material expert tests, media expert tests, and from student trials. The research instrument used was a feasibility sheet and student response questionnaires. Data analysis used descriptive qualitative and quantitative descriptive analysis. The conclusion from the results of this study is that the E-Module learning media with Flip Pdf Professional based on QR Code in PAI learning at SMAN Plandaan Jombang is very feasible to use with revisions with an average percentage given by the validator of 86.34%. The response of students to the E-Module learning media with Flip Pdf Professional based on QR Code in PAI learning at SMAN Plandaan Jombang is an average of 80% which means it has a very good predicate.